2020
DOI: 10.1111/jsap.13231
|View full text |Cite
|
Sign up to set email alerts
|

Cluster of cases of congenital feline goitrous hypothyroidism in a single hospital

Abstract: To describe the clinicopathological findings and outcomes of cases of feline congenital hypothyroidism diagnosed in a single veterinary hospital in Santiago, Chile. Materials and MethOds: Medical records were searched for cases of congenital hypothyroidism over an 18-month period. Inclusion criteria were a diagnosis of congenital hypothyroidism based on consistent historical and clinical findings, a low or low-normal serum total T4 and elevated serum canine TSH (cTSH). results: Six unrelated cats ranging in ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(35 citation statements)
references
References 28 publications
3
30
2
Order By: Relevance
“…Congenital hypothyroidism (CH) is a relatively uncommon disease in cats, with about 70 cases reported in the literature [ 1 , 2 , 3 ]. It has been suggested that CH is an under-recognized disorder as a significative proportion of cases are not diagnosed or die at birth or when juvenile, without the cause of death being established [ 1 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Congenital hypothyroidism (CH) is a relatively uncommon disease in cats, with about 70 cases reported in the literature [ 1 , 2 , 3 ]. It has been suggested that CH is an under-recognized disorder as a significative proportion of cases are not diagnosed or die at birth or when juvenile, without the cause of death being established [ 1 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…These signs include an enlarged broad head, a short neck and short limbs [ 1 ]. Additional findings are lethargy, mental dullness, constipation, hypothermia, bradycardia, prolonged retention of deciduous teeth, cold intolerance and retention of kitten hair, with the result that the coat remains soft and fluffy [ 1 , 3 , 4 , 5 , 6 , 7 ]. Clinicopathological abnormalities are non-specific and can include mild anemia, hypercholesterolemia, and azotemia [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital hypothyroidism was very unlikely since the dwarfism was not disproportionate, and the kitten was not mentally dull ( 10 ). The level of the thyroid hormone was in the low reference range at the beginning and normal while on therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism is caused by a developmental failure of the thyroid gland or by impaired thyroid hormone production. Clinical signs include disproportionate dwarfism (short body and limbs, big head), delayed tooth eruption, mental dullness, and lethargy ( 9 , 10 ). Hypoadrenocorticism was described in one dwarf kitten with clinical signs of neurological disorders, with behavioral changes characterized by excessive fear, recurrent episodes of tremors, weakness, severe hypothermia, dull and scruffy fluffy hair coat, dysorexia, and pica ( 11 ).…”
Section: Introductionmentioning
confidence: 99%